DOI: 10.17077/etd.03y9rc4t
|View full text |Cite
|
Sign up to set email alerts
|

Nurse manager competencies

Abstract: Building on a previous 1994 study, this descriptive study reflects on the evershifting sands of the nurse manager role. This national survey is based on the Katz (1955) conceptual framework of interrelated technical, human and conceptual competencies. An instrument developed by the investigator for determining important nurse manager competencies was validated using an expert panel of American Organization of Nurse Executive (AONE) Nurse Manager Fellows. The research used a web-based survey to collect informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…Other studies also consider being knowledgeable in various areas necessary for a head nurse. [ 4 ],[ 5 ],[ 11 ] The American Organization of Nurse Executives (2008) consider knowledge as one of the main dimensions of competence in a nursing manager, although a great part of this scientific knowledge pertains to the science of management and business. [ 12 ] The present study found management science and the knowledge of care and treatment to be more important than the knowledge of business management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies also consider being knowledgeable in various areas necessary for a head nurse. [ 4 ],[ 5 ],[ 11 ] The American Organization of Nurse Executives (2008) consider knowledge as one of the main dimensions of competence in a nursing manager, although a great part of this scientific knowledge pertains to the science of management and business. [ 12 ] The present study found management science and the knowledge of care and treatment to be more important than the knowledge of business management.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Chase (2010) also viewed certain attributes essential for a competent nursing manager, including good nursing care planning, clinical skills, the use of technology, respecting the standards of nursing care, and a good humor and optimism. [ 11 ] Nazari et al . (2016) also considers having a broad knowledge of healthcare and respecting professional ethics the requirements of a competent nursing manager.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…also showed that holding educational courses for the mangers increased their managerial skills to perform their managerial duties (organizing, daily activities, planning, motivating, conducting and supervising the staff and situations analysis). [ 25 ] Because decisiveness, counseling, work allocation, making efficient communication, coordination, conflict management, time management, organizing, planning, problem solving, support, education, performance evaluation, efficient discipline, and team work are among the most important capabilities that the operational managers should consider and administrate,[ 26 ] hiring the managers who are knowledgeable of managerial issues is realized in health care services centers. [ 21 ] Limitations of the present study included limitation in conducting similar studies in the studied wards and limitation concerning access to international articles in this field.…”
Section: Discussionmentioning
confidence: 99%